Animal welfare in South Africa : a multi-component programme design - Adams, Leanne (Institute for Monitoring and Evaluation, 2015)
The ongoing international atrocity of animal abuse is a persistent and widespread social problem within human society. The maltreatment of animals, particularly in rural impoverished contexts in South Africa continues to be a pertinent challenge facing local animal welfare organisations. Upon identifying the need to improve the conditions of animals living in the Darling community, the Swartland SPCA approached the evaluator in order to design a plausible humane education programme. The evaluator began this research by reviewing the history and underlying principles of humane education, the efficacy of humane education, as well as formalised humane education programmes. Findings from the review revealed that humane education programmes hold diminished capability for the achievement of improved animal welfare when implemented in isolation. Although these programmes aim to affect behavioural change in order to respond to the problem of animal welfare, behavioural change is not easily achieved with a simple intervention such as humane education. Thus, designing a programme for the Swartland SPCA based solely on the logic of humane education with the expectation of behavioural change was deemed problematic. Subsequently, the evaluator endeavoured to develop a novel programme design to target the problem of animal welfare in Darling. Increasingly, research points to the need for a multifaceted approach in dealing with the problem of animal maltreatment due to its complex nature as well as the fact that it is based on a large number of confounding personal, familial, social, cultural and psychological factors. To address this need, the evaluator, in consultation with the SPCA, identified a number of possible reasons as to why the problem of animal welfare was a prevalent issue within the Darling community. This highlighted the need for additional interventions that could be employed holistically to alleviate the problem of animal abuse. Given that this research concerns the welfare of animals in terms of human-directed behaviours, it was decided that humane education as a form of intervention should be investigated further in its ability to affect attitudinal change in conjunction with violence prevention and peer education / modelling interventions as additional programme components. In order to affect interpersonal violence at a behavioural level, a violence prevention component was selected with the hope that reductions in interpersonal violence may extent toward the reduction of violence and abusive behaviour towards animals. Finally, peer education / role modelling was selected as a means of involving community members in the promotion of animal welfare via the concepts developed from the humane education programme component. Since an improvement of animal welfare conditions is essentially dependant on the performance of individual behaviours, grounding the programme in a theory of behaviour change was identified as an important first step in the programme design. As such, Ajzen's theory of planned behaviour was utilised as a behaviour change model in order to guide the programme's design framework and to ensure that the programme components corresponded with theoretically identified mechanisms of behavioural change. It was anticipated that utilising a multidimensional programme design rooted in a theory of behaviour change would increase the likelihood of achieving the link between attitudinal change and behavioural change. Therefore, this evaluation provides the Swartland SPCA with a broad-based programme design which provides a variable-oriented insight into the proposed mechanisms of change and can be utilised as a framework in the adaption of programme components. It is envisioned that this tool be used by the programme stakeholders to decide on intended outcomes, select the programme activities, and further define the design details thereof. A number of recommendations are also made in order to assist with the successful implementation of this programme and its sub-components in the long term. These include lobbying for the inclusion of animal welfare and violence prevention content as part of national school curricula, obtaining a violence prevention partner organisation to assist with certain implementation considerations, and finally the importance of continuous community engagement and involvement prior to and during the programme’s roll out.